Flexible La0.67Sr0.33MnO3:ZnO Nanocomposite Thin Films Integrated on Mica - Zhang, Xiong; Yang, Hui; Wang, Guoliang; Zhang, Yi; Huang, Jijie (Frontiers in Materials, 2022)
The integration of functional oxide thin films on flexible substrates is critical for their application in flexible electronics. Here, to achieve flexible perovskite manganite oxide film with excellent low-field magnetoresistance (LFMR) effect, textured La0.67Sr0.33MnO3 (LSMO):ZnO nanocomposite film was deposited on a flexible mica substrate with ZnO buffer via pulsed laser deposition (PLD). Compare to the polycrystalline LSMO:ZnO nanocomposite film directly deposited on mica without buffer, LSMO:ZnO/ZnO/mica sample exhibits larger saturation magnetization (164 emu/cm3) and higher Curie temperature (~319K), which is resulted from the crystallinity and strain in LSMO phase. In addition, the LSMO:ZnO/ZnO/mica film presents a high MR value of ~39% at 10 K under 1 T. Furthermore, the good mechanical stretchability and property stability of the nanocomposite thin films have been demonstrated with mechanical bending.